2021
DOI: 10.1097/txd.0000000000001174
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplants in Controlled Donation Following Circulatory Death, or Maastricht Type III Donors, With Abdominal Normothermic Regional Perfusion, Optimizing Functional Outcomes

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, these studies did not compare the use of NRP with the widespread SRR. Ramirez et al found that DCD kidneys treated with NRP had a lower rate of DGF than those with SRR 27 . In a recent Spanish nationwide propensity score analysis, Padilla et al have found that NRP was associated with improved rates of DGF and 1-year graft loss compared to SRR 28 .…”
Section: Results Of Kts With Nrpmentioning
confidence: 99%
“…However, these studies did not compare the use of NRP with the widespread SRR. Ramirez et al found that DCD kidneys treated with NRP had a lower rate of DGF than those with SRR 27 . In a recent Spanish nationwide propensity score analysis, Padilla et al have found that NRP was associated with improved rates of DGF and 1-year graft loss compared to SRR 28 .…”
Section: Results Of Kts With Nrpmentioning
confidence: 99%